Protective effects of intermittent hypoxia on brain and memory in a mouse model of apnea of prematurity - Bouslama, Myriam; Adle-Biassette, Homa; Ramanantsoa, Nelina; Bourgeois, Thomas; Bollen, Bieke; Brissaud, Olivier; Matrot, Boris; Gressens, Pierre; Gallego, Jorge (Frontiers in Physiology, 2015)
Apnea of prematurity (AOP) is considered a risk factor for neurodevelopmental disorders in children based on epidemiological studies. This idea is supported by studies in newborn rodents in which exposure to intermittent hypoxia (IH) as a model of AOP significantly impairs development. However, the severe IH used in these studies may not fully reflect the broad spectrum of AOP severity. Considering that hypoxia appears neuroprotective under various conditions, we hypothesized that moderate IH would protect the neonatal mouse brain against behavioral stressors and brain damage. On P6, each pup in each litter was randomly assigned  to one of three groups: a group exposed to IH while separated from the mother (IH group), a control group  exposed to normoxia while separated from the mother (AIR group), and a group of untreated  unmanipulated pups left continuously with their mother until weaning (UNT group).  Exposure to moderate IH consisted of 20  hypoxic events/hour, 6 hours per day from postnatal day 6 (P6) to P10. The stress generated by maternal separation in newborn rodents is known to impair brain development, and we expected this effect to be smaller in the IH group compared to the AIR group. In a separate experiment, we combined maternal separation with excitotoxic brain lesions mimicking those seen in preterm infants. We analyzed memory, angiogenesis, neurogenesis and brain lesion size. In non-lesioned mice, IH stimulated hippocampal angiogenesis and neurogenesis and improved short-term memory indices. In brain-lesioned mice, IH decreased lesion size and prevented memory impairments. Contrary to common perception, IH mimicking moderate apnea may offer neuroprotection, at least in part, against brain lesions and cognitive dysfunctions related to prematurity. AOP may therefore have beneficial effects in some preterm infants. These results support the need for stratification based on AOP severity in clinical trials of treatments for AOP, to determine whether in patients with moderate AOP, these treatments are beneficial or deleterious.